2022
DOI: 10.1093/ehjci/jeac128
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous assessment of late gadolinium enhancement grey zone in patients with non-ischaemic cardiomyopathy with T1ρ and native T1 mapping

Abstract: Aims This study aims to validate and compare the feasibility of T1ρ and native longitudinal relaxation time (T1) mapping in detection of myocardial fibrosis in patients with non-ischaemic cardiomyopathy, focusing on the performance of both methods in identifying late gadolinium enhancement (LGE) grey zone. Methods and results Twenty-seven hypertrophic cardiomyopathy (HCM) patients, 16 idiopathic dilated cardiomyopathy (DCM) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…There was a moderate correlation between ECV and T1ρ and a mild correlation between ECV and native T1 in our study. The same findings were also reported in a previous study ( 18 ). The correlation between ECV and T1ρ suggests that the expansion of myocardial interstitial might be related to myocardial collagen deposition, but this needed to be verified by pathology.…”
Section: Discussionsupporting
confidence: 92%
“…There was a moderate correlation between ECV and T1ρ and a mild correlation between ECV and native T1 in our study. The same findings were also reported in a previous study ( 18 ). The correlation between ECV and T1ρ suggests that the expansion of myocardial interstitial might be related to myocardial collagen deposition, but this needed to be verified by pathology.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found that T 1ρ values were positively associated with T 1 values. The same results were also reported in the study of Dong et al 18 The native T 1 is affected by excessive collagen deposit (fibrosis) mainly through the interactions of water spin with surround magnetic dipole moments of neighboring molecules, whereas T 1ρ is mainly changed by chemical exchange between free water spins and collagenbounded spins. Both T 1 and T 1ρ have been demonstrated the capability for the detection of myocardial fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…Both T 1 and T 1 ρ have been demonstrated the capability for the detection of myocardial fibrosis 8,18 . Previous studies 8,18 also show the good correlation between T 1 and T 1 ρ . In addition, we also found that T 1 ρ values were positively associated with T 2 values.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations